Responsibility of Notaries in The Inclusion of The Names of Instrumentary Witnesses Who Were Not Present at The Signing of Authentic Deeds (Study of The Decision of The Rantau Prapat District Court Number 26 / Pdt.G / 2020 / PN RAP) - Adella Tanuwidjaja; Siti Hajati Hoesin (IHSA Institute, 2022)
In essence, the scope of the task of carrying out the position of a Notary is to make evidence as desired by the parties who appear to carry out a certain legal action. The case raised in this study originated from a lease agreement made before a Notary. Based on the applicable laws and regulations, the Notary is obliged to read the Deed in front of an audience in the presence of at least 2 witnesses, or 4 witnesses specifically for the making of a private will, and signed at the same time by the appearer, witness, and the Notary. However, the Notary in this case included the name of a witness in the relevant Lease Deed, even though the witness was actually not present on the day of making, reading, and signing of the deed by the parties. Therefore, one of the parties in the Lease Deed filed a lawsuit against the Notary because he felt aggrieved by the possibility that the Lease Deed would lose its proving power as an Authentic Deed because it did not meet the requirements as regulated in the laws and regulations. The main issue raised in this study is the responsibility of the Notary in including the name of the Instrumental Witness who was not present at the signing of the Authentic Deed and its implementation in the decision of the Rantau Prapat District Court Decision Number 26/Pdt.G/2020/PN RAP. This research is normative judicial research. The type of data used is secondary data obtained through literature study. To further elaborate the main issue, it is further described in the introduction, a discussion of the Instrumental Witness and the responsibilities of the Notary in relation to the inclusion of the name of the Instrumental Witness who was not present at the signing of the Authentic Deed, and closing.